Self Concept Training to Improve Future Orientation Among College Student - Wisnu Anendya Sekti; Chr. Hari Soetjiningsih; Adi Setiawan (PSIKODIMENSIA, 2019)
This research aim is to examine the effect of self concept training on future orientation among college student in Faculty of Psychology Satya Wacana Christian University. This study is a quasi-experimental research by one-group pretest-posttest design. Participant on this research are 20 college student from Faculty of Psychology Satya Wacana Christian University, whose selected by accidental sampling. The participant will receive a treatment namely self concept training which build from multidimensional model of self concept according to Fitts (Pauldine, Warren, & Swails, 2017). Future Orientation Questionnaire (FOQ), an instrument developed by Seginer (2009) is used to measure future orientation on participant before and after treatment. We also used paired sample t test to test the hypothesis in this research. Result showed that t score is 5,711 (t table = 2,093) and significance level is 0,000 (p